The Crisis of the Political. An Individual and the Cosmopolis - Kazlauskas, Raimondas (Sociologija. Mintis ir veiksmas, 2021)
The purpose of this paper is to identify the most important problems of the crisis of the political in the first stage of Western civilization – the Greek world in the IV–II centuries BC. The crisis of the political is treated as a unique constellation of political, supra-political, and apolitical factors. The paper explores a hypothesis of how the power elite eliminates the core features of the political – tensions of consciousness and natural human hostilities – and substitutes them with management techniques that cause public apathy towards previously established democratic institutions. A theatrical model of life with an intensified function of individualizing social roles is an unavoidable result of such processes.
Keywords: deification; Heimarmene; monarchy; nomos; individual; Tyche; theatre; the political